Investigation of potential use of waste lime sludge in bituminous binder. (2021) - Kanoungo, Abhishek; Kanwar, Varinder S; Goyal, Ajay; Kanoungo, Shristi
Abstract: The amount of waste generation has increased massively owing to the large production in manufacturing industries which has led to the problem of disposal for this waste. The wisest way to reduce the burden on landfills for disposal of waste is to utilize it in construction industry. Therefore, a study has been undertaken to use waste lime sludge containing CaCO3 from toothpaste industry to amend the properties of asphalt. In this paper, the conventional test of the modified binder prepared by adding waste sludge was compared to unmodified binder. Moisture susceptibility of modified binder was evaluated to check the moisture resistance and to evaluate the grade of bitumen the kinematic viscosity test was conducted. It was found that by adding waste lime sludge, soft grade bitumen was converted to hard grade and it showed better resistance to moisture damage.